Evaluación del desempeño del comportamiento organizacional en la Cooperativa Intercantonal de transporte Tosagua Asociada. - Loor Loor, Agustina Asunción (2018)
The investigation in the Cooperative Intercantonal of Transport Tosagua Associated had the purpose of evaluating the behavior of the organization, where initially a bibliographical study was used to determine the theoretical bases by means of the development of a matrix of authors that contained the variables applied by different researchers, who using the analysis and synthesis were determined those with greater applicability, resulting among these: productivity, absenteeism, staff turnover and job satisfaction; After that, the evaluation tool was structured (questionnaire), including a qualitative or Likert scale, with application indicators: always, almost always, sometimes and never. After evaluating the population under study, the data was processed and analyzed, accompanying the process through a qualitative-quantitative, analytical-synthetic methodology that would facilitate the execution of the diagnosis of the organizational environment and development of the improvement plan corresponding to the detected shortcomings. The application of the process described above generated viable results, which allow to reach the conclusion that the behavior of the Tosagua Intercantonal Transport Cooperative presents optimal performance in the variables productivity and job satisfaction with application rates of almost always corresponding to 63% and 73%. % respectively; in terms of absenteeism (39%) and turnover (56%), they present levels of alarm that require attention to optimize development, implementing improvement actions that reduce the bad practices detected.